A minireview on chemical vapor deposition growth of wafer-scale monolayer h-BN single crystals. Issue 41 (15th October 2021) - Li, Lin; Zhang, Ye; Zhang, Ruijie; Han, Ziyi; Dong, Huanli; Yu, Gui; Geng, Dechao; Yang, Hui Ying
Abstract : Recent academic breakthroughs in chemical vapor deposition (CVD) deposited h -BN are presented. The techniques, catalysts, and mechanisms are fully studied. The great advances in expanding the size of h -BN single crystals will largely push forward the way to h -BN. Abstract : Hexagonal boron nitride ( h -BN), with its excellent stability, flat surface, and large bandgap, plays a role in a variety of fundamental science and technology fields. The past few years have witnessed significant development in the scaled growth of h -BN single crystals. Currently, the size of h -BN crystal can be reached up to wafer-scale, paving the way towards industrial production and commercial applications. In this minireview, recent academic breakthroughs regarding the controlled growth of large-sized h -BN single crystals via chemical vapor deposition (CVD) are presented. The as-developed technique in terms of growth parameters, choice of catalysts, and the mechanism is fully emphasized, offering a guideline in enhancing the size and quality of h -BN. Several typical metal catalysts have been used in shaping scaled h -BN single crystals, of which the metal Cu substrate has drawn the most intensive attention. The significant advances in expanding the size of h -BN single crystals will largely push forward the way to h -BN industrialization and commercialization. The past few years have witnessed significant development in the scaled growth of h -BN single crystals. Currently, the size of h -BN crystal can be reached up to wafer-scale, paving the way towards industrial production and commercial applications. In this minireview, recent academic breakthroughs regarding controlled growth of large-sized h -BN single crystals via chemical vapor deposition (CVD) are present. The as-developed technique in terms of growth parameters, choice of catalysts and mechanism is fully emphasized, offering a guideline in enhancing size and quality of h -BN. Several typical metal catalysts are exhibited in shaping scaled h -BN single crystals, of which the metal Cu substrate has drawn the most intensive attentions.